Adopting human factors in early phase and experimental medicine research: a nested pilot study observing controlled human infection with SARS-CoV-2 - Higham, HE; Morgan, L; Cooper, C; Marshall, J; Mawer, A; Jackson, S; Lopez Ramon, R; Hughes, E; Richards, D; McShane, H; Fullerton, JN (Wiley, 2023)
Aims The influence of human factors on safety in healthcare settings is well established, with targeted interventions reducing risk and enhancing team performance. In experimental and early phase clinical research participant safety is paramount and safeguarded by guidelines, protocolized care and staff training; however, the real-world interaction and implementation of these risk-mitigating measures has never been subjected to formal system-based assessment.